Chitosan Derived Nanoparticles –based Sensing Probes for Detection of Japanese Encephalitis (JE) Antigen - Lai, Huat Choi (Universiti Malaysia Sarawak (UNIMAS), 2021)
Japanese encephalitis virus (JEV), a mosquito-transmitted flavivirus that will lead to neurological diseases and death in humans in extreme cases. Up to date, there are currently no specific anti-viral medications and curative treatment for JEV. Therefore, early, effective and accurate diagnosis of JEV infection by using a point-of-care, simple, rapid and economical biosensor is very critical for the prevention and control of JEV outbreaks. A biosensor is an analytical device containing biocatalyst and a transducer for point-of-care screening which converts any diseases or harmful biological events to detectable signals. Designing and fabricating biosensors with a higher rate of reaction and sensitivity has to become popular among researchers due to the emergence of nanotechnology. In recent decades, carbon nanoparticles (CNPs) have attracted numerous researchers to study their nanoscience and nanotechnology potential comparing to other nanoparticles due to their special characteristics especially their optical and electrochemical properties which turn them into potential candidates for bioimaging, biosensing, drug delivery, and photodynamic applications and most importantly CNPs are easier to synthesize, environmental friendly and low cost. In this study, based on the electrical conductivity performance of CNPs derived from the various types of precursor characterized by using cyclic voltammetry, (CV) and electrochemical impedance spectroscopy, (EIS), chitosan CNPs with the smallest size and performed highest electrical conductivity are selected for further modification in order to fabricate a higher rate of reaction and sensitivity of electrochemical biosensor. Carbon nanoparticles modified on screen-printed carbon electrode (CNPs-SPCE) electrochemical biosensor strip has been successfully fabricated by immobilized JEV antibody onto the surfaces of carbon nanoparticles through amide bonds formed between amino groups of CNPs and carboxylic groups of JEV antibody. The analytical performance of the CNPs- iv SPCE electrochemical biosensor strip was characterized using CV and EIS. CNPs-SPCE electrochemical biosensor strip exhibited a linear detection range of 1 − 20 ngmL−1 with a low limiyt of detection (LOD) of 0.36 ngmL−1 (at S/N = 3) for JEV, detection sensitivity was 0.024 ngmL−1 for JEV and analysis results were obtainable within 10 minutes. In order to enhance the sensitivity and selectivity of the CNPs-SPCE electrochemical biosensor strip, the addition of Gold nanoparticles (AuNPs) onto CNPs to produce the hybrid Gold-Carbon nanoparticles (Au-CNPs) which provides a higher effective surface area, catalytic activity and electrical conductivity has been successfully fabricated. The analytical performance of hybrid Gold-Carbon nanoparticles modified on screen-printed carbon electrode (Au-CNPsSPCE) electrochemical biosensor strips was characterized using CV and EIS. Au-CNPsSPCE electrochemical biosensor strip exhibited a linear detection range of 1 − 20 ngmL−1 with an extremely low LOD of 0.29 ngmL−1 (at S/N = 3) for JEV, detection sensitivity was 0.04 ngmL−1 for JEV and responding time is 10 minutes. The potential clinical application of this Au-CNPs-SPCE electrochemical biosensor strip was demonstrated by the detection of JEV in human serum while the selectivity of this biosensor strip was also proven by using Dengue antigen. In conclusion, virus infections can cause serious diseases to humans and animals as certain viruses could spread rapidly within a very short period. Hence, the fabrication of this accurate and fast biosensor for early detection of viruses is often crucial for clinical diagnosis and therapy